Silicon pools in human impacted soils of temperate zones. Issue 9 (22nd September 2015) - Vandevenne, F. I.; Barão, L.; Ronchi, B.; Govers, G.; Meire, P.; Kelly, E. F.; Struyf, E.
Abstract Besides well‐known effects of climate and parent material on silicate weathering the role of land use change as a driver in the global silicon cycle is not well known. Changes in vegetation cover have altered reservoirs of silicon and carbon in plants and soils. This has potential consequences for plant‐Si availability, agricultural yields, and coastal eutrophication, as Si is a beneficial element for many crop plants and an essential nutrient for diatom growth. We here examined the role of sustained and intensive land use and human disturbance on silicon (Si) pool distribution in soils with similar climatological and bulk mineralogical characteristics. We show that land use impacts both biogenic and nonbiogenic Si pools. While biogenic Si strongly decreases along the land use change gradient (from forest to croplands), pedogenic silica fractions (e.g. pedogenic clays) increase in topsoils with a long duration of cultivation and soil disturbance. Our results suggest that nonbiogenic Si pools might compensate for the loss of reactive biogenic silicon in temperate zones.